Spinning-grade all-aryl polynaphthyl ester resin and preparation method thereof

By introducing all aryl groups into the molecular structure of polynaphthalene resin, the rigidity and fluidity of the molecular segments are improved, and the problem of difficulty in spinning of polynaphthalene is solved, and high molecular weight all aryl polypolyses suitable for fibers is prepared. Naphthalene resin achieves the efficient preparation of polynaphthalene fibers.

CN119119438AActive Publication Date: 2024-12-13SICHUAN UNIV

Patent Information

Application Number
CN202411382017.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2024-12-13
Estimated Expiration
2044-09-30

AI Technical Summary

Technical Problem

During the spinning process, existing polynaphthalene resins are difficult to spin due to high glass transition temperature, high crystallization temperature, and poor melt fluidity. In addition, traditional preparation methods have harsh reaction conditions, high equipment requirements, and long time. Disadvantages, it cannot meet the preparation requirements of polynaphthalate fiber.

Method used

The polymerization reaction of para-hydroxybenzoic acid, 6-hydroxy-2-naphthoic acid, aromatic dicarboxylic acid and ethylene glycol monomer under catalyst action was carried out, and the spinning grade was prepared by polymerization at specific temperatures and vacuum conditions. All-aryl polynaphthalene resin improves the rigidity and fluidity of molecular chain segments.

Benefits of technology

The spinning grade all-aryl polynaphthalate resin with high molecular weight, low impurity content, good heat resistance and excellent fluidity was successfully prepared. It is suitable for the preparation of polynaphthalate fibers, significantly improving the feasibility of spinning molding.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119119438A_ABST
    Figure CN119119438A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of high polymer materials, and particularly relates to spinning-grade all-aryl polynaphthyl ester resin and a preparation method thereof. According to the invention, p-hydroxybenzoic acid, 6-hydroxy-2-naphthoic acid, aromatic dicarboxylic acid and ethylene glycol monomer are adopted as raw materials, polymerization reaction is carried out under the action of the catalyst, spinning-grade all-aryl polynaphthyl ester resin is successfully obtained under specific reaction conditions, and the spinning-grade all-aryl polynaphthyl ester resin has high molecular weight, low impurity content and good heat resistance, and can be used for preparing the spinning-grade all-aryl polynaphthyl ester resin. The melt fluidity is good, the shear thinning phenomenon is more obvious, and the method can be directly used for preparing the polynaphthalene ester fiber.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer materials, and in particular relates to a spinning-grade fully aromatic polynaphthyl ester resin and a preparation method thereof. Background Art

[0002] As a high-performance polymer material with naphthalene ring as the skeleton structure, polynaphthalene ester has a naphthalene ring structure on the molecular chain, and the main chain rigidity is significantly increased, so that it has excellent mechanical properties, thermal properties, barrier properties and radiation resistance. Polynaphthalene ester can be processed into fibers, films, sheets, etc., and used in high-end fields such as aerospace, atomic energy materials and other fields. Among them, polynaphthalene ester fibers can be used in high-end fields such as high-speed tires, ropes, special protection, etc. due to their strong mechanical properties, thermal properties and excellent stability. However, due to the increase in the rigid chain of polynaphthalene ester, a series of problems such as increased glass transition temperature, high crystallization temperature, and poor melt fluidity are triggered, which ultimately leads to the difficulty of spinning polynaphthalene ester. Developing spinning-grade polynaphthalene ester resins and improving the spinning process have become the main ways to solve this problem, among which spinning-grade polynaphthalene ester resins are fundamental.

[0003] At present, the preparation routes of polynaphthyl ester resin include direct esterification and transesterification. The direct esterification is similar to the reaction of PET, but due to the presence of naphthalene rings, the steric hindrance effect is increased, so the reaction conditions are extremely harsh and the purity of the monomer is high, and there are no industrialized products at present. The transesterification method is currently the most widely used method in industry. The process is divided into two parts. The first is melt transesterification. In this stage, the molecular weight is high, resulting in high melt viscosity, mass transfer and heat transfer problems, which easily cause uneven molecular weight distribution, and even carbonization increases impurities and poor batch stability. The second is solid phase polycondensation, which further increases the molecular weight of polynaphthyl ester, but the increase in molecular weight requires higher temperature and high vacuum conditions, has higher requirements on equipment, and has a long reaction time of up to tens of hours. The disadvantage of long cycle is self-evident.

[0004] As we all know, polymer fibers are obtained by melting, fiberizing, and winding polymer resins. Therefore, stable fiber molding requires that the polymer resin has excellent fluidity, a large molecular weight, a narrow distribution, and a low impurity content. Obviously, the polynaphthyl esters currently prepared by traditional methods cannot meet the requirements for the preparation of polynaphthyl ester fibers. Therefore, it is necessary to develop spinning-grade fully aromatic polynaphthyl ester resins. Summary of the invention

[0005] In order to solve the above problems, the present invention considers replacing the fat part with a fully aromatic group in the molecular structure, improving the rigidity of the molecular chain segments and thus reducing the entanglement between the molecular chain segments to greatly increase the fluidity and facilitate spinning.

[0006] Specifically, in one aspect, the present invention provides a method for preparing a spinning-grade wholly aromatic polynaphthyl ester resin, the preparation method comprising: using p-hydroxybenzoic acid, 6-hydroxy-2-naphthyl carboxylic acid, aromatic dicarboxylic acid and ethylene glycol monomers as raw materials, carrying out a polymerization reaction under the action of a catalyst to obtain a spinning-grade wholly aromatic polynaphthyl ester resin.

[0007] Furthermore, the polymerization reaction includes: first reacting at 210-240°C for 1.5-3h, then raising the temperature to 315-325°C at a rate of ≤3°C / min, reacting under vacuum for 0.5-3h, then reacting under nitrogen for 1-3h, crushing and drying the reaction product to obtain a fully aromatic polynaphthyl ester prepolymer, and finally reacting and extruding the prepolymer at 300-340°C and a vacuum degree of ≥0.07MPa for 5-20min, pelletizing and drying to obtain a spinning-grade fully aromatic polynaphthyl ester resin.

[0008] Furthermore, the preparation method also includes acetylation of the p-hydroxybenzoic acid and 6-hydroxy-2-naphthoic acid before the polymerization reaction, and the ethylene glycol monomer is ethylene glycol and acetylation of the ethylene glycol is performed before the polymerization reaction, or the ethylene glycol monomer is ethylene glycol diacetate.

[0009] Further, the acetylation of p-hydroxybenzoic acid, 6-hydroxy-2-naphthoic acid or ethylene glycol is achieved by using acetic anhydride at 135-155° C. for 3-5 h.

[0010] Furthermore, in the raw materials, according to molar percentage, the content of p-hydroxybenzoic acid is 60%-80%, the content of 6-hydroxy-2-naphthoic acid is 20%-32%, the content of aromatic dicarboxylic acid is 1%-6%, and the content of ethylene glycol monomer is 1%-6%.

[0011] Furthermore, the aromatic dicarboxylic acid is HOOC-Ar-COOH, wherein Ar is selected from

[0012] Further, the catalyst is selected from sulfuric acid, trifluoromethanesulfonic acid, methyl trifluoromethanesulfonate, titanium dioxide, ethylene glycol titanium, acetylacetonate titanium, n-butyl titanate, isopropyl titanate, ethylene glycol antimony, antimony trioxide, antimony acetate, stannous octoate, stannous oxalate, dibutyltin oxide, dibutyltin dilaurate, butylstannic acid, lithium acetate, potassium acetate, calcium acetate, magnesium acetate, barium acetate, zinc acetate, cobalt acetate, antimony acetate, lead acetate, manganese acetate, triisopropoxyaluminum, zinc acetate, zinc oxide, stannous chloride, concentrated sulfuric acid, p-toluenesulfonic acid, magnesium acetate, zinc acetate, zinc chloride, lithium chloride, germanium chloride, tin tetrachloride, potassium carbonate, triethylenediamine, triethylamine, zinc lactate, or a mixture of any proportions of any of the above.

[0013] Furthermore, the added amount of the catalyst is 1-1.5 wt% of the total weight of all reaction monomers.

[0014] Furthermore, the catalyst may be a mixture of magnesium acetate and n-butyl titanate. Furthermore, the mass ratio of magnesium acetate to n-butyl titanate in the mixture is 1:1 to 3:1.

[0015] In other aspects, the present invention provides a spinning-grade fully aromatic polynaphthyl ester resin obtained by the preparation method described herein.

[0016] In other aspects, the present invention provides the use of the spinning-grade fully aromatic polynaphthyl ester resin as described herein or obtained by the preparation method described herein in the preparation of polynaphthyl ester fibers.

[0017] Beneficial Effects of the Invention

[0018] The invention adopts p-hydroxybenzoic acid, 6-hydroxy-2-naphthoic acid, aromatic dicarboxylic acid and ethylene glycol monomers as raw materials, performs polymerization reaction under the action of a catalyst, and successfully obtains spinning-grade fully aromatic polynaphthyl ester resin under specific reaction conditions. The fully aromatic polynaphthyl ester resin has a higher molecular weight, a low impurity content, good heat resistance, good melt fluidity and exhibits a more obvious shear thinning phenomenon, and can be directly used for the preparation of polynaphthyl ester fibers. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 The picture shows the product obtained after spinning of the spinning-grade fully aromatic polynaphthyl ester resin prepared in the embodiment of the present invention.

[0020] Figure 2 The picture shows the product obtained after spinning of the wholly aromatic polynaphthyl ester resin prepared in the comparative example of the present invention. DETAILED DESCRIPTION

[0021] The present invention uses p-hydroxybenzoic acid, 6-hydroxy-2-naphthoic acid, aromatic dicarboxylic acid and ethylene glycol monomers as raw materials, and performs polymerization reaction under the action of a catalyst to obtain a spinning-grade fully aromatic polynaphthyl ester resin. The reaction route is as follows:

[0022]

[0023] The present invention is further described below with reference to specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0024] Example 1

[0025] This embodiment provides a spinning-grade fully aromatic polynaphthyl ester resin, which is prepared as follows:

[0026] (1) Acetylation of p-hydroxybenzoic acid: 10 mol (1380 g) of p-hydroxybenzoic acid and 15 mol (1531.4 g) of acetic anhydride were weighed and added into a 5 L reactor equipped with a stirrer, a thermometer, and a reflux condenser, and refluxed at 140° C. for 3 h to obtain a p-acetoxybenzoic acid solution; the solution was poured into cold water, washed with water and filtered for more than 3 times, and dried at 200° C. for 2 h (2-4 h) to obtain purified p-acetoxybenzoic acid with a purity of 98.8% (≥97.8%) and a yield of 96%;

[0027] (2) Acetylation of 6-hydroxy-2-naphthoic acid: 10 mol (1881.8 g) of 6-hydroxy-2-naphthoic acid and 15 mol (1531.4 g) of acetic anhydride were weighed and added into a 5 L reactor equipped with a stirrer, a thermometer and a reflux condenser, and refluxed at 140° C. (135-155° C.) for 3 h (3-5 h) to obtain a 6-acetoxy-2-naphthoic acid solution; the solution was poured into cold water, washed with water and filtered for more than 3 times, and dried at 200° C. for 2 h to obtain purified 6-acetoxy-2-naphthoic acid with a purity of 98.5% (≥97.8%) and a yield of 95%;

[0028] (3) Preparation of spinning-grade fully aromatic polynaphthyl ester resin: 3.25 mol (585.5 g) of purified p-acetoxybenzoic acid, 1.25 mol (284.78 g) of purified 6-acetoxy-2-naphthoic acid, 0.25 mol (36.54 g) of ethylene glycol diacetate (1%-6%), 0.25 mol (54.05 g) of 2,6-naphthalene dicarboxylic acid, and 1 wt% of the total weight of the monomers as catalysts of magnesium acetate and n-butyl titanate (the mass ratio of magnesium acetate to n-butyl titanate is 7:3) were weighed and added to a 5 L belt. In a reaction kettle with mechanical stirring, a reflux condenser and evacuable vacuum, the temperature is raised to 220°C for reaction for 2 hours, then the temperature is raised to 320°C at a rate of 0.5°C / min, the reaction is carried out under vacuum for 0.5 hours, nitrogen is filled into the reaction kettle, the reaction is carried out for 1 hour, the temperature is lowered and the material is discharged, and a wholly aromatic polynaphthyl ester resin prepolymer is obtained by crushing and drying; the prepolymer is added to a continuous polymerization device, reacted and extruded at a temperature of 320°C and a vacuum degree of 0.08MPa for 10 minutes, pelletized and dried to obtain a spinning-grade high molecular weight wholly aromatic polynaphthyl ester resin with a yield of about 80%.

[0029] The obtained spinning-grade fully aromatic polynaphthyl ester resin was tested, and the results were as follows: the intrinsic viscosity of the solution prepared with pentafluorophenol at 0.1 g / dL was 6.9 (5.6-8.7) at 60°C using an Ubbelohde viscometer, indicating that it has a relatively high molecular weight; the ash content measured in a high-temperature muffle furnace was less than 0.05% (≤0.14%), indicating that the impurity content was low; the thermal performance data measured by DCS and TGA showed that the melting point could reach 280°C, the thermal decomposition temperature could reach 500°C, and the residual carbon content at 800°C was 39.23%, indicating that it has good heat resistance; the viscosity of the resin at 300°C and 1Hz was 300 Pa.s (250-430 Pa.s) tested by a flat plate rheometer, and it showed a more obvious shear thinning phenomenon, indicating that the resin has excellent fluidity. The prepared fully aromatic polynaphthyl ester resin can be directly used for fiber preparation.

[0030] Figure 1 : is a picture of the product obtained after spinning of the spinning-grade fully aromatic polynaphthyl ester resin prepared in this example, indicating that the polynaphthyl ester fiber was successfully prepared.

[0031] Comparative Example 1

[0032] This comparative example provides a fully aromatic polynaphthyl ester resin, which is prepared as follows:

[0033] (1) Acetylation of p-hydroxybenzoic acid: 10 mol (1380 g) of p-hydroxybenzoic acid and 15 mol (1531.4 g) of acetic anhydride were weighed and added into a 5 L reactor equipped with a stirrer, a thermometer, and a reflux condenser, and refluxed at 133° C. for 3 h to obtain a p-acetoxybenzoic acid solution; the solution was poured into cold water, washed with water and filtered for more than 3 times, and dried at 200° C. for 2 h to obtain purified p-acetoxybenzoic acid with a purity of 97.5% and a yield of 92%;

[0034] (2) Acetylation of 6-hydroxy-2-naphthoic acid: 10 mol (1881.8 g) of 6-hydroxy-2-naphthoic acid and 15 mol (1531.4 g) of acetic anhydride were weighed and added into a 5 L reactor equipped with a stirrer, a thermometer, and a reflux condenser, and refluxed at 135° C. for 3 h to obtain a 6-acetoxy-2-naphthoic acid solution; the solution was poured into cold water, washed with water and filtered for more than 3 times, and dried at 200° C. for 2 h to obtain purified 6-acetoxy-2-naphthoic acid with a purity of 96.8% and a yield of 95%;

[0035] (3) Preparation of fully aromatic polynaphthyl ester resin: 3.25 mol (585.5 g) of purified p-acetoxybenzoic acid, 1.25 mol (284.78 g) of purified 6-acetoxy-2-naphthoic acid, 0.6 mol (87.696 g) of ethylene glycol diacetate, 0.6 mol (129.72 g) of 2,6-naphthalene dicarboxylic acid, and 1.2 wt% of the total weight of the monomers as catalysts of magnesium acetate and n-butyl titanate (the mass ratio of magnesium acetate to n-butyl titanate is 7:3) were weighed and added to 5 L of flask. In a reaction kettle equipped with mechanical stirring, a reflux condenser and a vacuum unit, the temperature is raised to 230°C for reaction for 2 hours, then the temperature is raised to 320°C at a rate of 5°C / min for reaction under vacuum for 1 hour, nitrogen is introduced into the reaction kettle, the reaction is continued for 1 hour, the temperature is lowered and the material is discharged, and the wholly aromatic polynaphthyl ester resin is obtained by crushing and drying; the prepolymer is added to a continuous polymerization device, reacted and extruded at a temperature of 315°C and a vacuum degree of 0.05MPa for 10 minutes, pelletized and dried to obtain a high molecular weight wholly aromatic polynaphthyl ester resin with a yield of about 78%.

[0036] The obtained high molecular weight fully aromatic polynaphthyl ester resin was tested, and the results were as follows: a 0.1 g / dL solution was prepared with pentafluorophenol, and the intrinsic viscosity was measured by Ubbelohde viscometer at 60°C to be 3.9; the ash content was measured in a high temperature muffle furnace to be 1.5%, indicating a high impurity content; the thermal performance data measured by DCS and TGA showed that the melting point could reach 265°C, the thermal decomposition temperature could reach 489°C, and the residual carbon content at 800°C was 37.37%, which had good heat resistance; the viscosity was 516 Pa.s at 300°C and 1Hz tested by a plate rheometer. The prepared fully aromatic polynaphthyl ester resin cannot be directly used for fiber preparation. These results show that even with the same raw materials, spinning-grade polynaphthyl ester cannot be obtained under different reaction conditions.

[0037] Figure 2 is a picture of the product obtained after spinning of the wholly aromatic polynaphthyl ester resin prepared in this comparative example, indicating that polynaphthyl ester fiber cannot be successfully obtained.

[0038] It should be noted that the preferred embodiments of the present invention are given in the specification of the present invention, but the present invention can be implemented in many different forms and is not limited to the embodiments described in this specification. These embodiments are not intended to be additional limitations on the content of the present invention. The purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive. In addition, the above-mentioned technical features continue to be combined with each other to form various embodiments not listed above, which are all considered to be within the scope of the present invention specification; further, for ordinary technicians in this field, they can be improved or transformed according to the above description, and all these improvements and transformations should belong to the protection scope of the claims attached to the present invention.

Claims

1. A method for preparing a spinning-grade fully aromatic polynaphthyl ester resin, It is characterized in that The preparation method comprises: using p-hydroxybenzoic acid, 6-hydroxy-2-naphthoic acid, aromatic dicarboxylic acid and ethylene glycol monomers as raw materials, carrying out polymerization reaction under the action of a catalyst to obtain a spinning-grade fully aromatic polynaphthyl ester resin; The polymerization reaction comprises: first reacting at 210-240°C for 1.5-3h, then raising the temperature to 315-325°C at a rate of ≤3°C / min, reacting under vacuum for 0.5-3h, then reacting under nitrogen for 1-3h, crushing and drying the reaction product to obtain a wholly aromatic polynaphthyl ester prepolymer, and finally reacting and extruding the prepolymer at 300-340°C and a vacuum degree of ≥0.07MPa for 5-20min, pelletizing and drying to obtain a spinning-grade wholly aromatic polynaphthyl ester resin.

2. The preparation method according to claim 1, It is characterized in that The preparation method further comprises acetylation of the p-hydroxybenzoic acid and 6-hydroxy-2-naphthoic acid before polymerization, and the ethylene glycol monomer is ethylene glycol and acetylation is performed before polymerization, or the ethylene glycol monomer is ethylene glycol diacetate.

3. The preparation method according to claim 2, It is characterized in that Acetylation of p-hydroxybenzoic acid, 6-hydroxy-2-naphthoic acid or ethylene glycol is achieved using acetic anhydride at 135-155°C for 3-5h.

4. The preparation method according to claim 1, It is characterized in that In the raw materials, according to molar percentage, the content of p-hydroxybenzoic acid is 60%-80%, the content of 6-hydroxy-2-naphthoic acid is 20%-32%, the content of aromatic dicarboxylic acid is 1%-6%, and the content of ethylene glycol monomer is 1%-6%.

5. The preparation method according to claim 1, It is characterized in that The aromatic dicarboxylic acid is HOOC-Ar-COOH, wherein Ar is selected from 6. The preparation method according to claim 1, It is characterized in that The catalyst is selected from sulfuric acid, trifluoromethanesulfonic acid, methyl trifluoromethanesulfonate, titanium dioxide, ethylene glycol titanium, acetylacetonate titanium, n-butyl titanate, isopropyl titanate, ethylene glycol antimony, antimony trioxide, antimony acetate, stannous octoate, stannous oxalate, dibutyltin oxide, dibutyltin dilaurate, butylstannic acid, lithium acetate, potassium acetate, calcium acetate, magnesium acetate, barium acetate, zinc acetate, cobalt acetate, antimony acetate, lead acetate, manganese acetate, triisopropoxyaluminum, zinc acetate, zinc oxide, stannous chloride, concentrated sulfuric acid, p-toluenesulfonic acid, magnesium acetate, zinc acetate, zinc chloride, lithium chloride, germanium chloride, tin tetrachloride, potassium carbonate, triethylenediamine, triethylamine, zinc lactate, or a mixture of any proportions of any of the above.

7. The preparation method according to claim 1, It is characterized in that The added amount of the catalyst is 1-1.5 wt% of the total weight of all reaction monomers.

8. The preparation method according to claim 6, It is characterized in that The catalyst is a mixture of magnesium acetate and n-butyl titanate; Furthermore, the mass ratio of magnesium acetate to n-butyl titanate in the mixture is 1:1 to 3:

1.

9. A spinning-grade wholly aromatic polynaphthyl ester resin obtained by the preparation method according to any one of claims 1 to 8.

10. Use of the spinning-grade wholly aromatic polynaphthyl ester resin according to claim 9 in the preparation of polynaphthyl ester fibers.

Citation Information

Patent Citations

  • Industrial preparation method for high-performance thermotropic liquid crystal polyester with homogeneous segmer structure

    CN104004170A

  • Fiber-grade thermotropic liquid crystal polyarylester and fiber product thereof

    CN116023638A

  • Method for manufacturing aromatic liquid crystalline polyester resin and aromatic liquid crystalline polyester resin compound

    KR1020140074095A

Cited By

  • Preparation method of triethylene glycol di-2-ethylhexoate

    CN120623042A

  • A process for the preparation of triethylene glycol diisooctylate

    CN120623042B

  • Spinning-grade wholly aromatic polynaphthoate resin and preparation method therefor

    WO2026066122A1